Time development of scour around pile groups in tidal currents. (1st September 2018) - Ma, Lili; Wang, Lizhong; Guo, Zhen; Jiang, Hongyi; Gao, Yangyang
Abstract: Local scour around pile foundations is a major factor affecting the foundation stability in ocean engineering. A series of experiments has been conducted to study the time development of scour around pile groups under the unidirectional and tidal currents. 49 cylindrical model piles were arranged in a typical dumbbell-shaped configuration, and 20 micro-cameras as well as a 3D laser scanner were used to capture the local scour topography. In the unidirectional current test, the scour pit was spoon-shaped, and the maximum scour depth was located in the central part of upstream pile group. In the tidal tests, two similar shallow scour pits existed in the upstream and downstream pile group. During the initial stage of tide-induced local scour, the increase of scour depth was similar to that under unidirectional current. But, the repetitive scour and backfill process led to obvious fluctuations of scour depth, especially for the piles at the rear of upstream pile group and in the front of downstream pile group. It was found that the tidal cycle number had obvious effect on the scour depth development. The final scour depth after sufficient tidal cycles could reach up to 77.1% of the maximum scour depth under unidirectional current. Highlights: Capture the development of local scour around a large pile group using 20 micro-cameras and a 3D laser scanner. Indentify and compare the characteristics of current and periodical tide induced scour pits around pile group. Assess the influence of tide number and period on tide scour.